Simon Peter in scripture and memory: the New Testament apostle in the early church - Bockmuehl, Markus (Baker Academic, 2012)
Peter in canon and memory. Simon Peter... in living memory? -- The New Testament Peter: an overview -- Peter in the "living memory" of East and West. The eastern Peter -- The western Peter -- History and memory: two case studies. How Peter became a disciple -- From unlikely birthplace to a global mission